Bacteriocin: A natural approach for food safety and food security - Dibyajit Lahiri; Moupriya Nag; Bandita Dutta; Tanmay Sarkar; Siddhartha Pati; Siddhartha Pati; Debarati Basu; Zulhisyam Abdul Kari; Lee Seong Wei; Slim Smaoui; Khang Wen Goh; Rina Rani Ray (Frontiers in Bioengineering and Biotechnology, 2022)
The call to cater for the hungry is a worldwide problem in the 21st century. Food security is the utmost prime factor for the increasing demand for food. Awareness of human health when using chemical preservatives in food has increased, resulting in the use of alternative strategies for preserving food and enhancing its shelf-life. New preservatives along with novel preservation methods have been instigated, due to the intensified demand for extended shelf-life, along with prevention of food spoilage of dairy products. Bacteriocins are the group of ribosomally synthesized antimicrobial peptides; they possess a wide range of biological activities, having predominant antibacterial activity. The bacteriocins produced by the lactic acid bacteria (LAB) are considered to be of utmost importance, due to their association with the fermentation of food. In recent times among various groups of bacteriocins, leaderless and circular bacteriocins are gaining importance, due to their extensive application in industries. These groups of bacteriocins have been least studied as they possess peculiar structural and biosynthetic mechanisms. They chemically possess N-to-C terminal covalent bonds having a predominant peptide background. The stability of the bacteriocins is exhibited by the circular structure. Up till now, very few studies have been performed on the molecular mechanisms. The structural genes associated with the bacteriocins can be combined with the activity of various proteins which are association with secretion and maturation. Thus the stability of the bacteriocins can be used effectively in the preservation of food for a longer period of time. Bacteriocins are thermostable, pH-tolerant, and proteolytically active in nature, which make their usage convenient to the food industry. Several research studies are underway in the domain of biopreservation which can be implemented in food safety and food security.